(untitled) (Bangladesh Journal of Animal Science, 2023)
Reproductive aging is influenced by a gradual decline in both the quantity and quality of oocytes found within ovarian follicles. In mammals, fertility relies heavily on the health of oocyte reserves, the dynamics of follicular development, and the functioning of the ovaries. This study aimed to investigate the impact of age on the follicular dynamics of goat ovaries. A total of 40 ovaries of Black Bengal goats were obtained from a local slaughterhouse and sorted into four age groups: 6-12 months, 13-15 months, 18-21 months, and 22-24 months. Subsequently, the ovaries were treated, and follicles were assessed through visually and histologically. The findings revealed that nearly all parameters, including weight, length, and width, of both ovaries in the 18-21 months age group were insignificantly different (p>0.05) from the other age groups. Histologically, the number of normal primordial and primary follicles was also insignificantly higher (p>0.05) in goats aged 18-21 months compared to the other age groups. Conversely, the quantity of secondary follicles significantly increased (p<0.05) with age, but in terms of antral follicles, a quadratic trend was observed, where they increased up to a certain age and then declined. Additionally, the results showed that the number of degenerated primary and antral follicles was significantly higher (p<0.05) in the ovaries of 22–24-month-old goats, while the number of degenerated secondary follicles was insignificantly higher (p>0.05) compared to the remaining age groups. In conclusion, age had an effect on the follicular dynamics of goat ovaries, suggesting that ovaries from goats aged 18-21 months, sourced from slaughterhouses, hold potential for quality follicles and oocytes that can be valuable for further research. Bangladesh Journal of Animal Science 52 (4): 88-97